2005
DOI: 10.1080/10288457.2005.10740585
|View full text |Cite
|
Sign up to set email alerts
|

“There is a worksheet to be followed”: A case study of a science teacher's use of learning support texts for practical work

Abstract: Drawing on the notion of the 'didactical transposition' of curriculum texts, this paper takes a critical look at why one science teacher still persists with a traditional teacher-centred approach towards practical work. It flows from a multi-case study on the instructional decision-making of Grade 9 Natural Science teachers currently implementing the new outcomes-based Curriculum 2005 in South Africa. Data were collected through classroom observations, prelesson and post-lesson interviews, video-stimulated rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 11 publications
1
18
1
Order By: Relevance
“…Skott's (2004) description of how curriculum standards can operate as a set of demands or obligations on teachers-rather than allowing for their pedagogical autonomy-suggests that curricular demands have the potential to interact with teachers' decisions given particular contexts. Similarly, Stoffels (2005) used a case study to argue that the decision-making of science teachers in South Africa could "at best be described as limited and passive" (Stoffels, 2005, p. 539) due to increased institutional demands.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Skott's (2004) description of how curriculum standards can operate as a set of demands or obligations on teachers-rather than allowing for their pedagogical autonomy-suggests that curricular demands have the potential to interact with teachers' decisions given particular contexts. Similarly, Stoffels (2005) used a case study to argue that the decision-making of science teachers in South Africa could "at best be described as limited and passive" (Stoffels, 2005, p. 539) due to increased institutional demands.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Stoffels (2005) indicated that teachers need a boost in confidence for them to operate competently. The study has shown this need.…”
Section: Resultsmentioning
confidence: 99%
“…Having to cover many topics for the external examinations may have resulted in teachers resorting to demonstrations. Teacher M also indicated that disciplinary issues (Stoffels, 2005) also led him to conduct demonstrations. Teacher B indicated that not having a laboratory assistant stops him from conducting many practical work tasks.…”
Section: Institutional and Practical Contextmentioning
confidence: 99%
See 2 more Smart Citations